(untitled) (Vallis Aurea, 2018)
Recent research suggests that greater business co-operation between enterprises is associated with a higher level of social capital of an individual. Since managers are basically people who base their activity on co-operation, the goal of this paper is to establish a link between the level of social capital of managers in cluster-based companies with their assessment of the activity and results of those activities in clusters. The analysis includes all dimensions and elements of social capital and the perception of managers on the business results of mutual cooperation. For this purpose, the Canonical correlation analysis (CCA) and the nonparametric statistical method (Kendall Tau-b correlation; τb) were used to avoid the conclusion using only one of the methods. The results have shown that there is a statistically significant, but weak, correlation between trust in institutions and active membership in associations with managers’ assessment of joint activities within the cluster. This research has shown that there is a statistically significant association between multiple memberships of managers in associations with their higher grade of activity within the cluster. The results have shown that general trust and perception of compliance with the norms of citizens is negatively associated with a higher grade of cluster activity, but these results are not statistically significant.